REDESIGN PERFORMANCE ASSESSMENT AS ASSESSMENT FOR LEARNING TO IMPROVE 21ST CENTURY HEALTH LITERACY - Fathimah, Ismah; Sari, Dian Ratna (BIOCHEPHY: Journal of Science Education, 2025)
This study aims to redesign performance assessment as Assessment for Learning to improve students' 21st century health literacy. The subjects in this study were 11th grade high school students in West Java, 2 classes as pilot classes and 1 class as a research class. The research method used is Research and Development (RnD) which is simplified with the ADDIE model consisting of analysis, design, development, implementation and evaluation stages. The redesigned assessment include tasks and rubrics that can improve students' 21st century health literacy based on the Partnership US-Based 21stst century skills (P-21) framework. The results of redesign performance assessment as assessment for learning at the implementation stage are quite effective with the number of students (48.6%) having N-gain in the high category and medium category (51.4%).